Comparison of calculated and measured basic dosimetric parameters for total body irradiation with 6- and 18-MV photon beams. Issue 1 (24th March 2021) - Hoseinnezhad, Elham; Geraily, Ghazale; Esfahani, Mahbod; Farzin, Mostafa; Gholami, Somayeh
Abstract: Purpose: Total body irradiation (TBI) is an external beam radiation therapy in which large field size and extended source skin distances (SSDs) are applied to deliver a therapeutic dose to the whole body. As measurements in such situations are not common and have more uncertainties in comparison to standard dosimetry situations, it is more precise if calculated beam data can be used instead of measurements taken under TBI situations. The purpose of this study is to compare calculated beam data [percentage depth dose (PDD) and dose rate] with those obtained from simulated treatment measurements. Materials and methods: PDD and dose rates were measured for the 6- and 18-MV photon beams under TBI and standard conditions using 9, 000 cm 3 water phantom and ion chambers (Markus and Farmer). The results were then compared with the calculated PDD and dose rate data. The beam flatness was also measured under TBI and standard conditions for both 6- and 18-MV photon beams, and the results were then compared. Results: A comparison of the measurement and calculated beam data shows that the difference between calculated and measured PDD values is −6·97 and −4·14% for the 6- and 18-MV photon beams, respectively. The ratio of calculated to measured dose rate was 1·09 and 1·02 for the 6- and 18-MV photon beams, respectively. The beam flatness under TBI conditions was 4·59% for 6-MV and 5·37% for 18-MV photon beam, whereas under standard conditions, these values were 1·50 and 1·98% for 6- and 18-MV radiation beams, respectively. Findings: According to the results, due to a high error level in dose rate and PDD calculations, these parameters must be directly measured under TBI conditions; however, regarding the obtained results, direct measurement is not necessary for the 18-MV photon beam.